Analisis Faktor Yang Mempengaruhi Praktek Penghindaran Pajak Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia Tahun 2015-2017 - Rokhanah Murkana; Yananto Mihadi Putra (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2020)
This study aims to analyze the factors that influence the practice of tax avoidance by using profitability, leverage, sales growth and the audit committee as independent variables. The method used is a purposive sampling method with population in the form of financial statements from 30 companies listed on the Indonesia Stock Exchange from 2015-2017, so that the sample of data observed is 90 company financial statements. The research design used is causal and descriptive. The data collected is in the form of secondary data from the financial statements of manufacturing companies. Where data analysis is performed using multiple regression statistical analysis. The results found that profitability and sales growth had a significant effect on the level of tax avoidance. While leverage and the audit committee do not significantly affect the level of tax avoidance.